Marine protected areas as socio-economic systems: a method for defining socio-economic criteria in marine planning - Pegorelli, Camila; De Andres, Maria; García-Onetti, Javier; Rayo, Silvia; García-Sanabria, Javier (Frontiers in Marine Science, 2024)
This research aims to define socio-economic criteria for prioritizing proposals related to new marine protected areas, boundary adjustments, area relocations, and network corridors within marine management approaches. The study also focuses on identifying ecosystem services (ES) that address the social dimensions of various spatial management approaches in the marine realm. The presented method quantifies nature’s significance to human communities through stakeholder perceptions, bridging the gap between human activities and ecosystem services. The research defines essential socio-economic criteria, identifies the corresponding ecosystem services, and assesses their societal values within the socio-ecological system of a specific area, thereby enhancing the effectiveness of marine management processes such as marine spatial planning and marine protected areas.